2006
DOI: 10.1038/sj.bjc.6603030
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of prostatic metastatic migration towards human bone marrow stoma by Omega 6 and its inhibition by Omega 3 PUFAs

Abstract: Epidemiological studies have shown not only a relationship between the intake of dietary lipids and an increased risk of developing metastatic prostate cancer, but also the type of lipid intake that influences the risk of metastatic prostate cancer. The Omega-6 polyunsaturated fatty acid, Arachidonic acid, has been shown to enhance the proliferation of malignant prostate epithelial cells and increase the risk of advanced prostate cancer. However, its role in potentiating the migration of cancer cells is unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 44 publications
8
118
1
2
Order By: Relevance
“…Bone marrow stroma control and AA, previously shown to induce maximum PC-3 invasion (Brown et al, 2006), induced significant invasion through Matrigel ( Figure 1A). Common dietary oils failed to induce significant invasion compared with controls.…”
Section: Dietary Oils Do Not Induce Invasion But Their Pufa Componenmentioning
confidence: 99%
See 3 more Smart Citations
“…Bone marrow stroma control and AA, previously shown to induce maximum PC-3 invasion (Brown et al, 2006), induced significant invasion through Matrigel ( Figure 1A). Common dietary oils failed to induce significant invasion compared with controls.…”
Section: Dietary Oils Do Not Induce Invasion But Their Pufa Componenmentioning
confidence: 99%
“…As migrating CaP cells within the BMS take up lipids (Brown et al, 2006) we utilised mBM-Ad pulsed with D 8 -AA to determine whether these cancer cells take up lipids released from the mBM-Ad into the BMS environment or whether the process is mediated through direct interaction with the adipocytes themselves. A white light micrograph (Figure 3) shows a mBM-Ad overlaid with the FTIR spectral maps correlating to the vibrational spectral characteristics u(C -D) and u( ¼ C-D) of D 8 -AA and demonstrates clearly that D 8 -AA lies within the adipocyte.…”
Section: Cap Cells Within Bms Migrate To and Interact With Adipocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous AA and its lipid metabolites have been shown to induce ERK activation [40]. Several studies have demonstrated that specific inhibitors of COX and LOX reduce the incidence of development and metastasis of breast cancer tumors in animal models [41][42][43][44] and in humans [43]. Furthermore, COX-2 inhibitors can inhibit the growth of HBx-positive HCC cells [45].…”
Section: -Test)mentioning
confidence: 99%